If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-x-5/3=5
We simplify the equation to the form, which is simple to understand
2x-x-5/3=5
Simplifying:
2x-x-1.66666666667=5
We move all terms containing x to the left and all other terms to the right.
+2x-1x=+5+1.66666666667
We simplify left and right side of the equation.
+1x=+6.66666666667
We divide both sides of the equation by 1 to get x.
x=6.66666666667
| -4(3x+2)-5= | | 9=3n-6 | | 6(y-1)+3(-2y+2)= | | 8x+7+2x+x-3= | | 3(x+1)-25=7x-4(x+9) | | 46-7x=20x+16 | | 4(6)-(-2*-2)= | | 7-10x=47-38x | | 2(2x-1)=9 | | 3a^2-7a=20 | | y = -2x+6 | | 2(7x-(7-3y+6x)+2y)= | | Y+Y=24 | | 5x+34=17x+14 | | 5x+34=17x+18 | | 9x-4=-8 | | 8(u-8)=-5u-38 | | -10x-3(x-2)= | | 2y=9(4)-4x | | 10x+15=2x+21 | | 8(u-8)=-5-38 | | t^2+3t-10=0 | | 2x+5=-40-7x | | x/2-(2x+1)/6=(x+1)/3 | | 8(u-8)=-5lu-38k | | x(21-2x)(39-2x)= | | -10z^2+11z=3 | | 5t-(t-2)=2-3.(t-5) | | 71-6x=39x+21 | | 13-8x=173-36x | | 5x^2+8=2x | | 7(t+4)+3(2t-5)= |